Neotypification of Onuphis fukianensis Uschakov & Wu, 1962 and description of a new species of Onuphis (Annelida: Onuphidae) from China seas - Wu, Xuwen; Xu, Kuidong (Zootaxa, 2017)
The original description as well as illustrations of Onuphis fukianensis Uschakov & Wu, 1962 from the East China Sea is simple and no type material is available. The species is peculiar in the genus Onuphis by having very long ceratophores (40 rings on the lateral antennae) and a late start of branched branchiae (chaetiger 47) and thus transferred to the genus Heptaceras. Examination of newly collected material from the region of the type locality allowed us to demonstrate that the reassignment was incorrect. To clarify the status of the species, we designate a neotype and redescribe O. fukianensis. Our examination of historic material revealed another species of Onuphis, which also has relatively long ceratophores and pectinate branchiae that is described below as Onuphis uschakovi sp. nov. The new species highly resembles O. eremita parva Berkeley & Berkeley, 1941, a subspecies described from the southern coast of California. However, the two taxa can be easily distinguished by the number of ceratophoral rings (27–32 vs. 21), the start of subacicular hooks (chaetigers 12–13 vs. chaetiger 8) and the shape of pectinate chaetae (oblique with 8–10 teeth vs. transverse with 15 teeth).